Elastic, structural and optical studies on ᵪNa₂O-(35-ᵪ)V₂O₅-65TeO₂,ƴWO₃-(40-y)Ag₂O-60TeO₂ AND zNb₂O₅-(20-z)BaO-80TeO₂ tellurite based glass systems / Muhammad Umair Mohamad - Mohamad, Muhammad Umair (2015)
Three glass systems with composition xNa₂O- (35-x)V₂O₅-65TeO₂;(x=5,10, 15, 20, 25 mol %), yWO₃-(40-y)Ag₂O-60TeO₂ (y=0, 10, 20, 30 mol %) and zNb₂O₅-(20-z)BaO-80TeO₂ (z=0, 5, 10, 15 mol %) were prepared by conventional solid state and melt-quenching methods. Elastic moduli and structural changes were studied by measuring ultrasonic shear and longitudinal velocities using the pulse-echo-overlap technique and Raman spectroscopy, respectively. For xNa₂O-(35-x)V₂O₅-65TeO₂ glass system, both longitudinal (vL) and shear (vs) velocities showed small steady decrease with addition of Na₂O from x=5 mol % to x=15 mol % followed by large decrease at x>15 mol %. Longitudinal modulus (CL), shear modulus (μ), Young’s modulus (Y), Hardness (H) and Debye Temperature (θD) also showed similar behavior to the ultrasonic velocities. The decrease in elastic moduli is suggested to be due to weakening of network rigidity of the glass system with increase in formation of non-bridging oxygen (NBO) as revealed by Raman spectroscopy...